COMPARATIVE ANALYSIS OF MULTIMOORA, WASPAS AND WISP METHODS: THE CASE OF CANDIDATE SELECTION - Stanujkic, Maja (Journal of process management and new technologies, 2023)
This article conducts a comparative examination of three Multi-Criteria Decision Making (MCDM) methods: Multi-Objective Optimization by Ratio Analysis plus Full Multiplicative Form (MULTIMOORA), Weighted Aggregates Sum Product Assessment (WASPAS), and Simple Weighted Sum Product (WISP). The analysis is carried out within the context of a personnel selection problem, focusing exclusively on income attributes in the MCDM framework. The results obtained from the analysis, specifically the formulated ranking lists, reveal a consensus in selecting the same alternative as the most suitable across all three MCDM methods. However, there are partial discrepancies in the ranking lists of alternatives, highlighting variations in their assessments.
Keywords: human resources management; personnel selection; recruitment; MULTIMOORA; WASPAS; WISP; MCDM